The aging kidney is characterized by tubuloinflammaging, a phenotype associated with MHC-II gene expression - Sinning, Julius; Funk, Nils David; Soerensen-Zender, Inga; Wulfmeyer, Vera Christine; Liao, Chieh Ming; Haller, Hermann; Hinze, Christian; Schmidt-Ott, Kai Martin; Melk, Anette; Schmitt, Roland (Frontiers in Immunology, 2023)
Introduction Even during physiologic aging, the kidney experiences a loss of mass and a progressive functional decline. This is clinically relevant as it leads to an increased risk of acute and chronic kidney disease. The kidney tubular system plays an important role in the underlying aging process, but the involved cellular mechanisms remain largely elusive. Methods Kidneys of 3-, 12- and 24-month-old male C57BL/6J mice were used for RNA sequencing, histological examination, immunostaining and RNA-in-situ-hybridization. Single cell RNA sequencing data of differentially aged murine and human kidneys was analyzed to identify age-dependent expression patterns in tubular epithelial cells. Senescent and non-senescent primary tubular epithelial cells from mouse kidney were used for in vitro experiments. Results During normal kidney aging, tubular cells adopt an inflammatory phenotype, characterized by the expression of MHC class II related genes. In our analysis of bulk and single cell transcriptional data we found that subsets of tubular cells show an age-related expression of Cd74, H2-Eb1 and H2-Ab1 in mice and CD74, HLA-DQB1 and HLADRB1 in humans. Expression of MHC class II related genes was associated with a phenotype of tubular cell senescence, and the selective elimination of senescent cells reversed the phenotype. Exposure to the Cd74 ligand MIF promoted a prosenescent phenotype in tubular cell cultures. Discussion Together, these data suggest that during normal renal aging tubular cells activate a program of ‘tubuloinflammaging’, which might contribute to age-related phenotypical changes and to increased disease susceptibility.